Le corps conjugué - Neumann, Hélène (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
Abstract Manon De Pauw's photographic and videographic work stands out for its ludic liveliness, the richness of its formal compositions, and its poetically evocative power. De Pauw explores the playful relationship between the body and space in a formalist approach through which the work is constructed by doing, by touch, by experiment. Although her works are self-referential, they are not predominantly psychological or emotional; the body functions, rather, as a "motif of the work." They evoke the need to go "off the clock" from routine, to reflect on one's position in the social corpus and on the room left to the imagination.